2019
DOI: 10.1007/978-3-030-02899-2_25
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Language Proficiency Tests in Higher Education

Abstract: In higher education, standardized academic language proficiency test scores are often used for multiple purposes, including admissions of international students to degree programs and identification of students' post-entry language support needs. In this chapter, issues surrounding the use of high-stakes standardized academic language proficiency tests for making decisions about international English as-a-second-language (ESL) students are explored. Specifically, a) stakeholders' views and knowledge about stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Further, the significant efficacy of the EP programme in relation to students' SGPA in the current study echoed prior research that locally designed EP programmes and tests seemed to be advantageous due to their alignment with the institutional curriculum, and can be potentially more representative of students' true competence than internationally standardised EP tests that might be less representative due to coaching and test preparation effects (Coombe and O'Sullivan, 2012; Ockey and Gokturk, 2019). In the context of Singapore, in particular, it is of great importance for higher education institutions to develop and evaluate their EP programme for both admission and placement decisions, which would better cater to the bi/multilingual speakers speaking English as their first language.…”
Section: Conclusion and Practical Implicationssupporting
confidence: 75%
See 1 more Smart Citation
“…Further, the significant efficacy of the EP programme in relation to students' SGPA in the current study echoed prior research that locally designed EP programmes and tests seemed to be advantageous due to their alignment with the institutional curriculum, and can be potentially more representative of students' true competence than internationally standardised EP tests that might be less representative due to coaching and test preparation effects (Coombe and O'Sullivan, 2012; Ockey and Gokturk, 2019). In the context of Singapore, in particular, it is of great importance for higher education institutions to develop and evaluate their EP programme for both admission and placement decisions, which would better cater to the bi/multilingual speakers speaking English as their first language.…”
Section: Conclusion and Practical Implicationssupporting
confidence: 75%
“…In addition, universities have also been accepting alternative forms of EP evidence such as locally developed language tests (Cho and Bridgeman, 2012; Oliver et al , 2012), which has been described to be beneficial due to their alignment with the local curriculum (Coombe and O'Sullivan, 2012). It was argued that the results of locally developed tests could be more representative of students' true competence levels than those of internationally standardised EP test, considering that students might have intentionally prepared for the internationally standardised tests and hence, could perform above their actual proficiency levels (Ockey and Gokturk, 2019). Moreover, results of locally developed EP tests could serve as direct references about how to assign different students into relevant levels of EP courses in the university after being admitted.…”
Section: Ep As a Moderator Of Sgpa And Why Evaluate Epmentioning
confidence: 99%
“…In many standard‐setting studies that compare standardized and local placement test scores, it is assumed that the local placement test is the criterion on which the standardized test should be judged (Kokhan, 2012; Ockey & Gokturk, 2019; Papageorgiou & Cho, 2014; Xi, 2007). To support this assumption, this study examined teachers’ judgments of the degree to which their students needed and were benefiting from an oral communication course.…”
Section: Discussionmentioning
confidence: 99%
“…It should be acknowledged that there are inherent limitations to judging the appropriateness of using standardized test scores for placement decisions based on criterion measures, given that criterion measures themselves may not be an accurate reflection of appropriate placement (Ockey & Gokturk, 2019). For instance, whereas Kokhan’s (2012) study found a difference between placement decisions based on the local placement test and TOEFL iBT, it did not answer the question of which test better placed students and it assumed that the local placement tests are valid and reliable instruments.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation